Which Skills Matter in the Market for CEOs? Evidence from Pay for CEO Credentials - Falato, Antonio; Li, Dan; Milbourn, Todd (Management Science, 2015)
Market-based theories predict that differences in CEO skills lead to potentially large differences in pay, but it is challenging to quantify the CEO skill premium in pay. In a first step toward overcoming this empirical challenge, we code detailed biographical information for a large sample of CEOs for a panel of S&P 1500 firms between 1993 and 2005 to identify specific reputational, career, and educational credentials that are indicative of skills. Newly appointed CEOs earn up to a 5% or $280,000 total pay premium per credential decile, which is concentrated among CEOs with better reputational and career credentials, those with the very best credentials, and those who run large firms. Consistent with the unique economic mechanism of market-based theories, CEO credentials have a positive impact on firm performance. The performance differential for newly appointed CEOs is up to 0.5% per credential decile and is also concentrated among CEOs with better reputational and career credentials and those at large firms. Credentials are positively correlated with unobserved CEO heterogeneity in pay and performance, which further validates our hypothesis that boards use them as publicly observable signals of otherwise hard-to-gauge CEO skills. In all, our results offer direct evidence in support of market-based explanations of the overall rise in CEO pay. This paper was accepted by Itay Goldstein, finance.